PENGARUH STRATEGI PROMOSI DAN SEGMENTASI PASAR TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PADA PT. MUTIARA TIMOR STAR KUPANG - Banur, Maria M.; Fanggidae, Ronald P.C.; Foenay, Christien C. (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2021)
This research was conducted on consumers of PT. Mutiara Timor Star Kupang. The purpose of this study was to determine the effect of promotional strategies and market segmentation partially and simultaneously on purchasing decisions for Honda motorbikes. This research used a qualitative descriptive method approach. The sample data collection used a simple random sampling method. Samples involved in this study were 100 respondents taken from distributed questionnaires, interviews as well as observations to consumers of PT. Mutiara Timor Star Kupang as the primary data source, and reports on Honda motorcycle sales data obtained as secondary data sources. The data analysis technique used in this research was descriptive statistical analysis test, multiple linear regression test, T test, F test, and determination coefficient test using the SPSS version 21 software program. The results of this study indicated that in the paartial approach, the promotional strategy variable did not influence the purchasing decision, while market segmentation variables influenced the purchasing decision. In simultaneous approach, however, the promotional strategy and market segmentation variables influenced the purchasing decisions for Honda motorbikes at PT. Mutiara Timor Star Kupang. Keywords: Promotion Strategy, Market Segmentation, Purchasing Decisions